Diagnosis and management of pyothorax in a domestic ferret (Mustela putorius furo). Issue 4 (9th May 2017) - Sladakovic, Izidora; Brainard, Benjamin M.; Lane, Selena L.; Secrest, Scott A.; Fox, Andrew J.; Tarigo, Jaime L.; Yeuroukis, Corry K.; Sanchez, Susan; Proenca, Laila M.; Mayer, Joerg
Abstract: Objective: To describe the diagnosis, management, and outcome of pyothorax in a domestic ferret ( Mustela putorius furo ). Case Summary: A domestic ferret was evaluated for a history of lethargy, anorexia, and pyrexia. Pleural effusion was detected with radiography and ultrasonography, and a diagnosis of pyothorax was made following cytologic evaluation of pleural fluid. Bilateral thoracostomy tubes were placed for thoracic drainage and lavage, and the ferret was treated with intravenous crystalloid fluids, antimicrobials, and analgesics. Bacterial culture of the pleural fluid yielded Fusobacterium spp. and Actinomyces hordeovulneris . This treatment protocol resulted in resolution of pyothorax, and a positive clinical outcome. New or Unique Information Provided: This is the first reported case of successful management of pyothorax caused by Fusobacterium spp. and A. hordeovulneris in a ferret.